Estudio y diseño del puente sobre la quebrada Quillán, parroquia de Químiag, cantón Riobamba, provincia de Chimborazo. - Avellaneda Buñay, Carina Alexandra (2016)
Bridges are structural elements that facilitate crossing streets, rivers and other geographical features. To build them is necessary to take into account hydrological, geological, topographical conditions and traffic flow in the area where they will be implanted. Territorial topographical characteristics are a very important points to deduce the importance of the bridges in the development of roads and land communication in Químiag parish; where flat areas are crossed by rivers, streams or ravines. Besides the countless benefits that structural bridges provide, they could be economic development and social in rural populations too. A bridge over Quillán ravine has been designed by applying the standards of A.A.S.H.T.O "American Association of State Highway and Transportation Officials", for bridges and "A.A.S.H.T.O. Guide for Design of pavement Structures" for pavement design entrances, which have been adopted by the M.T.O.P Ministerio de Transportes y Obras Públicas, for this type of project. In the structural design process, the L.R.F.D method was applied "Load and Resistance Factor Design", which is supported by complementary norms and standards such as Norma Ecuatoriana de la Construcción N.E.C. 2015. Also, the provisions of the American Concrete Institute A.C.I. - 318 and the standards of the American Society of Testing Materials A.S.T.M. After having analyzed all standardized requirements, this research purposes a concrete bridge, because this material can be applied to any structural construction system; additionally, its construction is more economical in the long term. This bridge will have a span of 22.50 m, an armed board (10, 40 x 22,50 x 0,20 m.).; 4 is composed beams (1,60 x 0,40 m.), will be settled on 4 supports Elastomeric (0,35 x 0,30 x 0,04 m.) and 2 open stirrups with predefined structural design measures.